Bis(4-methyl-N-{(2Z,4E)-4-[(4-methylphenyl)imino]pent-2-en-2-yl}anilinido)zinc - Anthony E. Wetherby; Benjamin A. Vaughan; Rory Waterman (Acta Crystallographica Section E, 2012)
The title compound, [Zn(C19H21N2)2], appears to be the first example of a zinc complex supported by two β-diketiminate (nacnac) ligands. This complex crystallizes with a distorted tetrahedrally coordinated ZnII atom that diposes the two nacnac ligands approximately orthogonally to one another [angle between the two N—Zn—N mean planes is 89.91 (10)°], with average Zn—N bond lengths of 1.992 (4) Å.